ВОПРОСЫ МЕТОДОЛОГИИ ЭНЕРГЕТИЧЕСКОГО ОБСЛЕД ОВАНИЯ ПРОМЫШЛЕННЫХ ПРЕДПРИЯТИЙ - Умурзакова, Г.Р. (Educational Research in Universal Sciences, 2023)
The article contains a number of comprehensive energy surveys to identify energy conservation reserves at industrial enterprises of various industries, the conduct of an energy survey, which becomes mandatory.